Creation of a Yeast Strain with Co‐Translationally Acylated Nucleosomes - Wu, Dan; Zhang, Yunfeng; Tang, Zhiheng; Chen, Xiaoxu; Ling, Xinyu; Li, Longtu; Cao, Wenbing; Zheng, Wei; Wu, Jiale; Tang, Hongting; Liu, Xiaoyun; Luo, Xiaozhou; et al. (Angewandte Chemie International Edition, 2022)
Structurally diverse acylations have been identified as post‐translational modifications (PTMs) on histone lysine residues, but their functions and regulations remain largely unknown. Interestingly, in nature, a lysine acylation analog, pyrrolysine, is introduced as a co‐translational modification (CTM) through genetic encoding. To explore this alternative life form, we created a model organism Saccharomyces cerevisiae containing site‐specific lysine CTMs (acetyl‐lysine, crotonyl‐lysine, or another synthetic analog) at histone H3K56 using non‐canonical amino acid mutagenesis to afford a chemically modified nucleosome in lieu of their own in vivo. We further demonstrated that acetylation of histone H3K56 partly tends to provide a more favorable chromatin environment for DNA repair in yeast compared to crotonylation and crosstalk with other PTMs differently. This study provides a potentially universal approach to decipher the consequences of different histone lysine PTMs in eukaryotes. An engineered yeast strain was created by replacing genomic histones with mutants using an optimized yeast genetic code expansion (GCE) system. It can survive with co‐translationally modified nucleosomes at the H3K56 position, providing insight into the functional differences in lysine acylation states, which might otherwise be difficult to study. Phenotypic variation between lysine acetylation and crotonylation was observed in this strain.